2010
DOI: 10.1111/j.1468-036x.2009.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Terrorist Attacks on International Stock Markets

Abstract: We examine the effects of terrorist attacks on stock markets, using a dataset that covers all significant events and that directly relate to the major economies of the world. Our event study suggests that terrorist attacks produce mildly negative price effects. We compare these price reactions to those from an alternative type of unanticipated disaster, earthquakes, and find that price declines following terror attacks are more pronounced. However, in both cases prices rebound within the first week of the afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
112
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(124 citation statements)
references
References 27 publications
10
112
0
2
Order By: Relevance
“…Furthermore, incidents that occurred in richer and more democratic countries and those in which human capital was destroyed induced a stronger negative market reaction. Instead of focusing on individual companies, Brounrn and Derwall (2010) examined the behavior of stock market indices in countries where terrorist attacks have taken place. They found that the abnormal return amounted to -0.92% on the event day -a more powerful response compared to that caused by earthquakes.…”
Section: This Is the Post Review Final Submitted Author Manuscript Amentioning
confidence: 99%
“…Furthermore, incidents that occurred in richer and more democratic countries and those in which human capital was destroyed induced a stronger negative market reaction. Instead of focusing on individual companies, Brounrn and Derwall (2010) examined the behavior of stock market indices in countries where terrorist attacks have taken place. They found that the abnormal return amounted to -0.92% on the event day -a more powerful response compared to that caused by earthquakes.…”
Section: This Is the Post Review Final Submitted Author Manuscript Amentioning
confidence: 99%
“…The event's specific characteristics have surfaced as a vital element of stock market reaction. Indicatively, Brounrn and Derwall (2010) suggested that terrorism incidents have a greater economic impact, especially on the day of the event, compared with unanticipated natural catastrophes, whereas Chesney et al (2011) argued that the latter exhibit longer post-event impact due to the delay in measuring their actual catastrophic effects. Moreover, Aslam and Kang (2015) posited that the location, type, intensity (measured by the number of fatalities), and tactics of the attack affect stock market behavior, whereas Essaddam and Karagianis (2014) argued that the geographic location in which the attack occurred influenced its overall impact.…”
Section: Non-macro Events Of Instability and Stock Markets' Behaviormentioning
confidence: 99%
“…Overall, research suggests that such incidents cause drastic, but short-term transitory effects on stock markets, especially on the first day, with recovery in most cases occurring within one to two days (Brounrn & Derwall, 2010;Chesney et al, 2011;Drakos, 2010). Kollias, Papadaumou and Stagiannis (2011), by contrasting the stock behavior following the attacks in Madrid (2004) and London (2005), suggested that recovery may be affected by both the type of the attack, and the promptness and adequacy of the country's institutional responses, an argument that is supported by Essaddam and Karagianis (2014), and Aslam and Kang (2015).…”
Section: Non-macro Events Of Instability and Stock Markets' Behaviormentioning
confidence: 99%
See 2 more Smart Citations